Exploiting the Imperialist Competition Algorithm to determine exit door efficacy for public buildings. (January 2014) - Kamkarian, Pejman; Hexmoor, Henry
The Imperialist Competition Algorithm has recently shown superior performance in optimizing goals. This algorithm has inspired us to apply it to exit doors. The Imperialist Competition Algorithm is applied to an environment to find the best possible locations for exit doors and also to estimate the minimum required width for each door in order to be able to rapidly evacuate a crowd out of danger in emergency situations. The results of our system are applied to a few prototypical scenarios that have demonstrated that the location of each exit door in an indoor space can play a significant role in the evacuation of a crowd out of an emergency situation. Our results thus far are promising and future work will account for more complex floor layouts.